T Cell Immune Profiles of Blood and Tumor in Dogs Diagnosed With Malignant Melanoma - Sparger, Ellen E.; Chang, Hong; Chin, Ning; Rebhun, Robert B.; Withers, Sita S.; Kieu, Hung; Canter, Robert J.; Monjazeb, Arta M.; Kent, Michael S. (Frontiers in Veterinary Science, 2021)
Investigation of canine T cell immunophenotypes in canine melanomas as prognostic biomarkers for disease progression or predictive biomarkers for targeted immunotherapeutics remains in preliminary stages. We aimed to examine T cell phenotypes and function in peripheral blood mononuclear cells (PBMC) and baseline tumor samples by flow cytometry, and to compare patient (n = 11-20) T cell phenotypes with healthy controls dogs (n = 10-20). CD3, CD4, CD8, CD25, FoxP3, Ki67, granzyme B and interferon-gamma (IFN-gamma) were used to classify T cell subsets in resting and mitogen stimulated PBMCs. In a separate patient cohort (n=11), T cells were classified using CD3, CD4, CD8, FoxP3 and granzyme B in paired PBMC and single cell suspensions of tumor samples. Analysis of flow cytometric data of individual T cell phenotypes in PBMC revealed specific T cell phenotypes including FoxP3+ and CD25+FoxP3- populations that distinguished patients from healthy controls. Frequencies of IFN-gamma + cells after ConA stimulation identified two different patient phenotypic responses, including a normal/exaggerated IFN-gamma response and a lower response suggesting dysfunction. Principle component analysis of selected T cell immunophenotypes also distinguished patients and controls for T cell phenotype and revealed a clustering of patients based on metastasis detected at diagnosis. Findings supported the overall hypothesis that canine melanoma patients display a T cell immunophenotype profile that is unique from healthy pet dogs and will guide future studies designed with larger patient cohorts necessary to further characterize prognostic T cell immunophenotypes.